2008
DOI: 10.1007/s10620-008-0549-7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Operator Fatigue on Endoscopy Performance: Implications for Procedure Scheduling

Abstract: Colonoscopy cecal intubation rates appear to decline with successive procedures. There also appears to be a trend for insertion times to lengthen. Reassuringly, other quality indicators of colonoscopy (lesion detection and withdrawal time) and EGD duration do not appear to be impacted by repetitive procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
32
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 19 publications
2
32
0
Order By: Relevance
“…Both studies suggested endoscopist fatigue as a possible factor, which has also been suggested as a reason for colonoscopy insertion times increasing with successive procedures. 24 In comparison, PDR does not decrease within our shifts 1 and 2, when the majority of procedures are completed, nor does PDR steadily decrease across shift of day. These results suggest that shorter shifts may be a possible solution to the progressive decline in PDR seen with longer shifts, although our shift 3 experiences the same phenomenon.…”
Section: Discussionmentioning
confidence: 63%
“…Both studies suggested endoscopist fatigue as a possible factor, which has also been suggested as a reason for colonoscopy insertion times increasing with successive procedures. 24 In comparison, PDR does not decrease within our shifts 1 and 2, when the majority of procedures are completed, nor does PDR steadily decrease across shift of day. These results suggest that shorter shifts may be a possible solution to the progressive decline in PDR seen with longer shifts, although our shift 3 experiences the same phenomenon.…”
Section: Discussionmentioning
confidence: 63%
“…[1][2][3] It is possible that fatigue may play a role in detecting fewer polyps later in an endoscopic work shift. [1][2][3]5 In the present study, we tested an inexpensive and minimally invasive informational poster, based on the tenets of social influence theory, 13 to stabilize the relationship between time of day and polyp yield in our unit. We hypothesized that an informational poster would remind clinicians to remain vigilant by enhancing awareness about time of day and polyp yield.…”
Section: Discussionmentioning
confidence: 99%
“…This was also hypothesized in a study from Ireland that evaluated the impact of procedure chronology on quality benchmarks in patients undergoing colonoscopy. 5 The authors concluded that cecal intubation rates decreased with successive procedures and attributed this finding to operator fatigue. 5 Fatigue is also well known to affect outcomes in other fields marked by repetitive activities.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This also has been hypothesized in a study from Ireland evaluating the effect of procedure chronology on quality benchmarks in patients undergoing colonoscopy. 16 Those authors concluded that cecal intubation rates declined with successive procedures, and they attributed this finding to operator fatigue. 16 So there are now data from teaching, 11,12 nonteaching, 14 VA, 11 non-VA, [12][13][14]16 U.S., [11][12][13][14] and European 16 centers that at least raise time of day as a possible factor affecting colonoscopy outcomes.…”
mentioning
confidence: 99%